(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The success and safety of the construction of buildings and structures largely depends on the geological and hydrological conditions of the construction site. Before construction work begins, it is very important to obtain accurate information about the physical and mechanical properties of the soil, underground structures, and water resources.